Review of the Police Code of Ethics on Accepting Bribes in the Practice of Embalming - Cahyani, Wilda; Basrawi, Basrawi; Nasir, Liana; Murniani, Murniani; Zulkarnain, Muh Dicky Try; Nurhikma, Nurhikma (Sangia Nibandera Law Research, 2025)
The police are agencies that carry out and maintain order, security, and law enforcement throughout Indonesia. The police institution has a crucial role in carrying out its duties. However, in reality, there are still many members of the police who do inappropriate things and violate the provisions stipulated in the Police Professional Code of Ethics as stipulated in Law No. 2 of 2002 concerning the Police Code of Ethics. This study aims to analyze law enforcement against police members involved in bribery practices in fines, as well as identify the obstacles faced in the law enforcement process. Effective law enforcement is essential to maintain the integrity of police institutions and ensure justice for the community. However, the practice of bribery involving police members often hampered the law enforcement function itself. Through a qualitative approach, this study found that factors such as entrenched culture of corruption, lack of internal oversight, and public fear of reporting, became significant obstacles in cracking down on police members who received bribes. In addition, complicated legal processes and support from certain parties in the power structure have made the situation worse. This study recommends the need for reforms in the surveillance system, ethics education for police members, and increased protection for whistleblowers to create a more transparent and accountable law enforcement environment.